Visualizing pairing symmetry in nematic superconductors using spin-polarized spectroscopy of magnetic impurities. (3rd October 2019) - Chen, Liang; Zhang, Ya-Li; Han, Rong-Sheng
Abstract: We study the spin-polarized spectral properties of Yu–Shiba–Rusinov resonance states induced by magnetic impurities in 2- and 3-dimensional nematic superconductors: few layer Bi2 Te3 grown on FeTe0.55 Se0.45 (2D) and Cu x Bi2 Se3 (3D). We focus on the relationship between pairing symmetry and the spatial structure of spin-polarized spectroscopy. We calculate the spin-polarized local density of states (SP LDOS) and the corresponding Fourier transformation using the T -matrix method for both the 2- and 3-dimensional materials. Various situations with different impurity orientations and different SP LDOSs have been investigated. We find that, like the quasiparticle interference spectrum, the spin-polarized spectroscopy can be applied to distinguish threefold rotation symmetric pairings, e.g. the plain s -wave pairing, chiral p  -wave pairing, etc, and nematic pairings in these materials.